The Sausapor Declaration: Challenges in promoting good governance to protect customary communities and natural resources in Tambrauw district, West Papua - Fatem, Sepus M.; Syuf, Yaved; Baru, Josepina; Marwa, Jonni; Runtuboi, Yubelince Y.; Tawer, Viktor; Situmorang, Saur; Runtuboi, Ferawati R. (Forest and Society, 2020)
The Sausapor Declaration has served as a stepping stone towards convening and balancing the dynamics of governmental politics, conservation efforts, the protection of customary communities’ rights, and the sustainable management of natural resources in Tambrauw District. The Declaration supported the establishment of Tambrauw as a Conservation District, while also acknowledging the rights of customary communities in shaping political priorities of the local government, which include: a) stewardship of extensive remaining tropical forests (91.9% forest cover); b) management of protected areas, which represent 77-80% of the total area of the District; c) acknowledging the cultural traditions of five major indigenous groups; and, d) securing the active support of formal institutions for these goals. Two stages have shaped the effort to establish the Conservation District.  The first stage involved the period prior to the formal declaration, while the second ecompasses development and implementation of related policies.  Establishing local regulations and protecting local communities required extensive lobbying with the provincial and national government, as well as advocacy in various seminars, including both national and international conferences that provided strategic opportunities for securing support for the Conservation District. These steps have been instrumental in gaining legitimacy and public support for relevant conservation policies and for protecting the rights of customary communities. As one example, the review of Tambrauw spatial planning documents  (RTRW) led to prioritizing eco-tourism as a leading sector for economic development, along with the creation of an overall agropolitan and renewable energy strategy.